Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Karyawan Generasi Z di Indomaret Sumenep - Alfin Drajatiana Wajdi; Chamariyah Chamariyah; Subijanto Subijanto (Trending: Jurnal Manajemen dan Ekonomi, 2025)
Generation Z is the most diverse generation and is distinctly different from previous generations. Generation Z prioritizes personal growth and development. However, this generation also has weaknesses, such as being indecisive due to a preference for speed or instant gratification, getting bored easily, and often acting impulsively without considering the surrounding situation or conditions.This study aims to examine the influence of organizational culture and work environment on the performance of Generation Z employees. The research method used is quantitative. The sampling technique applied is purposive sampling, with a population of 92 individuals, consisting of employees of PT Indomarco Prismatama (Indomaret) in the Sumenep region. The results of the study show that organizational culture does not have a significant effect on the performance of Generation Z employees. However, the work environment significantly influences the performance of Generation Z employees. Keywords: , , Organizational Culture, Work Discipline